PELATIHAN PENGENALAN DAN PENANGANAN TANDA-TANDA BAHAYA KEHAMILAN PADA IBU HAMIL DALAM UPAYA MENURUNKAN KASUS KEMATIAN IBU DI PUSKESMAS TURI - Eka Sarofah Ningsih; Fitriani Iktiarinawati F; Dhesi Indriany Asbanu (Jurnal Abdimas Bina Bangsa, 2023)
The aim of implementing this community service activity is to increase the understanding and ability of pregnant women to recognize early the danger signs of pregnancy and immediately seek help so that mothers and babies are safe and have an impact on reducing the maternal mortality rate. As well as increasing the understanding and ability of pregnant women and their families in early detection of danger signs during pregnancy. The output target achieved is to be able to provide another color in the implementation of the training so that it is useful for creating and developing thought patterns and sparking ideas related to the development of science and technology for the community in implementing the Tri Dharma of Higher Education. The results of this service still found pregnant women in the risk category for the dangers of pregnancy in the form of age over 30 years and the results of examination of hemoglobin levels still found mothers with hemoglobin levels less than normal. The evaluation results of counseling activities using several methods showed an increase in mothers' knowledge. Training activities for handling early detection of danger signs for pregnant women. Armed with this knowledge and vigilance, pregnant women can intensively carry out prevention efforts and prepare for early handling